Utilization of Wordwall Applications in Cognitive Development in Early Childhood - Wahyuni, Sri Eti; Asmawulan, Tri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to describe the use of the Wordwallapplication in developing the cognitive abilities of early childhood students at BA Aisyiyah Kalimandi. The background of this research is based on the importance of cognitive stimulation during the golden age, which requires teachers to present engaging, contextual, and technology-based learning experiences. Wordwall, as an interactive digital learning medium, is believed to create enjoyable learning experiences through educational game-based activities. This research employed a descriptive qualitative approach involving teachers and group B students at BA Aisyiyah Kalimandi. Data were collected through observation, interviews, and documentation, and analyzed using the interactive Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results indicate that the implementation of Wordwall enhances children's logical thinking, pattern recognition, and problem-solving abilities. Moreover, it increases learning motivation and encourages active participation in the learning process. These findings affirm that interactive digital media such as Wordwall can serve as an effective alternative for early childhood education when aligned with children's developmental stages and characteristics.